KESALAHAN PELAFALAN KOSAKATA DIFTONG DAN BUKAN DIFTONG SISWA BIPA 1 DI DAVAO CITY - FILIPINA - Marlia Marlia (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract: BIPA students in Davao City - the Philippines mostly use Visaya in their daily lives. In addition, some of them are still affected by Spanish in the pronounciation of the sounds of the language. This is the main influence of pronounciation errors in Indonesian vocabulary. This research examines the pronunciation of vocabulary with diphthong and not diphthong in Bahasa Indonesia. The purpose of this analysis is to describe the mistakes of BIPA students in pronouncing diphthong double vowels and not diphthongs and to explain the solutions that can be done to minimize these errors. The method used is descriptive qualitative. The finding in this research is that there are errors in vocal pronunciation of double diphthong and not diphthong. As many as 96% recite the double diphthong correctly and 4% still pronounce incorrectly. 67% recite double vowels instead of diphthongs being diphthongs and 33% recite double vowels separately (read every letter in the final syllable). This happens because of three things. First, the influence of the Visaya language. Second, the influence of Spanish. Third, the presence of allophones in Indonesian vowels. These problems can be overcome in three ways. First, through spoken-syllable techniques. Second, through the technique of imitation. Third, through repeated words. Through this research, it is expected to be able to help BIPA students in reciting Indonesian vocabulary, especially duplicate vocabulary, so that pronunciation errors can be minimized.Abstrak: Siswa BIPA di Davao City – Filipina mayoritas menggunakan bahasa Visaya dalam kehidupan sehari-harinya. Selain itu, sebagian di antara mereka masih terpengaruh bahasa Spanyol dalam pelafalan bunyi bahasa. Hal inilah menjadi pengaruh utama kesalahan pelafalan dalam kosa kata bahasa Indonesia. Riset ini mengkaji pelafalan kosa kata bervokal rangkap diftong dan bukan diftong bahasa Indonesia. Tujuan dilakukan analisis ini adalah mendeskripsikan kekeliruan siswa BIPA dalam pelafalan vokal rangkap diftong dan bukan diftong serta memaparkan solusi yang dapat dilakukan untuk meminimalkan kesalahan tersebut. Metode yang digunakan adalah deskriptif kualitatif. Temuan dalam riset ini adalah adanya kekeliruan pelafalan vokal rangkap diftong dan bukan diftong. Sebanyak 96% melafalkan vokal rangkap diftong dengan benar dan 4% masih melafalkan salah. Sebanyak 67% melafalkan vokal rangkap bukan diftong menjadi diftong dan 33% melafalkan vokal rangkap secara terpisah (dibaca per huruf di silabel akhir). Hal ini terjadi disebabkan oleh tiga hal. Pertama, pengaruh bahasa Visaya. Kedua, pengaruh bahasa Spanyol. Ketiga, adanya alofon dalam vokal rangkap bahasa Indonesia. Masalah-masalah tersebut dapat diatasi melalui tiga cara. Pertama, melalui teknik ucap – silabel. Kedua, melalui teknik ucap – tiru. Ketiga, melalui ucap – ulang. Melalui riset ini, diharapkan dapat membantu siswa BIPA dalam melafalkan kosa kata bahasa Indonesia, terutama kosa kata bervokal rangkap, sehingga kesalahan pelafalan dapat diminimalkan.